2022
DOI: 10.1177/00033197221124778
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Mortality of Patients After Transcatheter Aortic Valve Implantation: A Systematic Review and Meta-analysis

Abstract: While TAVI is widely used, optimal medical therapy to reduce the mortality rate after transcatheter aortic valve implantation (TAVI) is still unclear. We performed a systematic review and meta-analysis to evaluate the impact of statins on mortality following TAVI. Present systematic review of the literature was performed using Medline, Embase, Scopus, and Web of Science; all studies reported all-cause mortality in patients who underwent TAVI and received or did not receive statin therapy. Data were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Based on information from Refs. [ [1] , [2] , [3] , [4] , [5] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [32] , [33] , [34] , [35] , [36] , [37] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. The elements of the figure were created using SERVIER MEDICAL ART (CC BY 4.0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on information from Refs. [ [1] , [2] , [3] , [4] , [5] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [32] , [33] , [34] , [35] , [36] , [37] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. The elements of the figure were created using SERVIER MEDICAL ART (CC BY 4.0).…”
Section: Discussionmentioning
confidence: 99%
“…The use of statins in patients undergoing TAVI contributes to overall all-cause mortality risk reduction (HR = 0.78; 95 % CI: 0.68–0.89), which is more pronounced with the intensive statin therapy (HR = 0.62; 95 % CI: 0.45–0.85) [ 23 ]. It was also shown that the use of statins in patients undergoing SAVR reduced the risk of all-cause mortality (HR = 0.67; 95 % CI: 0.60–0.74).…”
Section: Lipoprotein (A)mentioning
confidence: 99%